Pengaruh Lingkungan Kerja terhadap Loyalitas Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi di The Axana Hotel Padang - Syevira Putri Gusti Amanda; Arif Adrian (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to determine: (1) the influence of the work environment on job satisfaction; (2) the influence of job satisfaction on employee loyalty; (3) the influence of the work environment on employee loyalty; (4) the influence of the work environment on employee loyalty with job satisfaction as an intervening variable. This study is a quantitative study. The population in this study were employees of The Axana Hotel. The research sample was 89 respondents. Data collection was carried out using a distributed questionnaire method. The data analysis technique used was regression analysis supported by the classical assumption test, F test, and path analysis test, with the help of the SPSS version 25.0 program. The results of the data analysis showed that the work environment had a positive and significant effect on job satisfaction with a Beta value or Standardized Coefficient of 0.261 with t count (2.523) with a significance of 0.013 <0.05. Job satisfaction has a positive and significant effect on employee loyalty with a Beta or Standardized Coefficient value of 0.338 with a t count (3.346) with a significance of 0.001 <0.05. The work environment has a positive and significant effect on employee loyalty with a Beta or Standardized Coefficient value of 0.605 with a t count (7.087) with a significance of 0.000 <0.05. And the work environment has a positive and significant effect on employee loyalty with satisfaction as a mediating variable at TheAxana Hotel. This can be seen in the results of the path analysis which produces a total influence value greater than the direct influence (0.693> 0.088).